Transnasal and standard transoral endoscopies in the screening of gastric mucosal neoplasias - Nakata, Hiroya (Baishideng Publishing Group Co., Limited, 2011)
AIM: To compare the diagnostic performances of transnasal and standard transoral esophagogastroduodenoscopy (EGD) in gastric cancer screening of asymptomatic healthy subjects. METHODS: Between January 2006 and March 2010, a total of 3324 subjects underwent examination of the upper gastrointestinal tract by EGD for cancer screening, with 1382 subjects (41.6%) screened by transnasal EGD and the remaining 1942 subjects (58.4%) by standard transoral EGD. Clinical profiles of the screened subjects, detection rates of gastric neoplasia and histopathology of the detected neoplasias were compared between groups according to the stage of Helicobacter pylori (H. pylori)-related chronic gastritis. RESULTS: Clinical profiles of subjects did not differ significantly between the two EGD groups, except that there were significantly more men in the transnasal EGD group. During the study period, 55 cases of gastric mucosal neoplasias were detected. Of these, 23 cases were detected by transnasal EGD and 32 cases by standard transoral EGD. The detection rate for gastric mucosal neoplasia in the transnasal EGD group was thus 1.66%, compared to 1.65% in the standard transoral EGD group, with no significant difference between the two groups. Detection rates using the two endoscopies were likewise comparable, regardless of H. pylori infection. However, detection rates when screening subjects without extensive chronic atrophic gastritis (CAG) were significantly higher with standard transoral EGD (0.70%) than with transnasal EGD (0.12%, P < 0.05). In particular, standard transoral EGD was far better for detecting neoplasia in subjects with H. pylori-related non-atrophic gastritis, with a detection rate of 3.11% compared to 0.53% using transnasal EGD (P < 0.05). In the screening of subjects with extensive CAG, no significant differences in detection of neoplasia were evident between the two endoscopies, although the mean size of detected cancers was significantly smaller and the percentage of early cancers was significantly higher with standard transoral EGD. CONCLUSION: These results strongly suggest that the diagnostic performance of transnasal endoscopy is suboptimal for cancer screening, particularly in subjects with H. pylori-related non-atrophic gastritis.